Not Quite Equal Odds: Openness to Experience Moderates the Relation Between Quantity and Quality of Ideas in Divergent Production - Friis-Olivarius, Morten; Christensen, Bo T. (Frontiers in Psychology, 2019)
Since brainstorming was introduced as a technique in 1953 it has been assumed that the best way to produce good ideas is through the production of many ideas, which has later been named the equal-odds rule. However, this finding that productivity often leads to creative quality has rarely been examined in psychometric studies of creative cognition. To close this knowledge gap, we examined the relationship between individual differences in creative personality, as assessed by the personality trait openness to experience, and both the quantity and quality of ideas produced in a divergent thinking task. Across 154 graduate students we found a positive and significant relationship between creative personality and the number of ideas produced, as well as their creative value. The present results indicate that while quantity does breed quality in creative production, the effect is moderated by individual differences, specifically the personality trait Openness to Experience. As the level of Openness to Experience increases, the relation of quantity of ideas to average Creative value gradually becomes positive and significant. We discuss the possible reasons for and implications of our findings.